SYMPTOMATOLOGY FOLLOWING COVID-19 VACCINATION – A CROSS-SECTIONAL STUDY IN CENTRAL INDIA - VIBHA ARJARIA,; DEEPIKA BADKUR,; VIKAS PANDEY, (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: A successful COVID-19 vaccine should survive the safety, efficacy, and potency testing phases without causing any negative side effects, especially in high-risk individuals, such as the elderly, pregnant women, people with comorbidities, health-care workers, and others. The present study was conducted to determine common symptoms following the COVID-19 vaccine, the intensity of symptoms after the first and second doses, and estimate the prevalence of acquiring COVID-19 infection after getting vaccinated with the COVID-19 vaccine. Methods: An observational cross-sectional study was conducted in the rural field practice area, including 445 participants from 19 villages. The statistical analysis was done using Microsoft Excel, and the data were represented in frequency and graphs. Results: In the present study, the maximum (74%) of participants were Covishield recipients. The top three symptoms experienced after the first dose were headache (189), fever (130), and pain in the arm at which the vaccine was given (77). After the second dose, the top three symptoms were fever (281), headache (137), and fatigue (73). The top three psychosomatic symptoms were increased sleep (162), decreased sleep (122), and the third ranker was anxiety (93). More participants reported having severe symptoms after the first dose than after the second. Three percent of research participants contracted COVID-19 infection after the first dose, and 2% after the second. Conclusion: Fever and headache were common symptoms after the first and second doses, but symptoms were more severe after administration of the first dose of the COVID-19 vaccine. Following vaccination, COVID-19 infection was extremely rare among participants.